Pelatihan Penyusunan Soal Penguasaan Kosakata Dalam Pembelajaran Sastra Untuk Tim MGMP Bahasa Indonesia Tingkat Sma Se-Pekanbaru - Rika Ningsih; Fatmawati Fatmawati; Noni Andriyani; Erni Erni; Alber Alber (Smart Education, 2021)
Abstract: Vocabulary is an important thing that must be possessed by a student in Indonesian language lessons, including literature lessons. To measure the extent to which the students' vocabulary mastery, the teacher needs to test the students. Before doing the test, of course, the teacher needs questions in measuring students' vocabulary mastery. The phenomenon found in the field is that teachers pay less attention to indicators in making literary questions. This causes the questions made to be not in accordance with the student's abilities so that the expected results are not achieved properly. The teacher's lack of skill in making literary questions, especially about vocabulary mastery, is caused by several factors. One of the factors is the lack of upgrading and training provided to teachers. The purpose of this PkM activity is to provide understanding to teachers in preparing vocabulary mastery questions in learning literature. There are several conclusions that can be drawn after carrying out this community service activity. First, the participants of the PkM activity (the teachers of the MGMP team at the high school level throughout Pekanbaru) were very enthusiastic about participating in this training. Second, after conducting training and discussions with teachers, four indicators were obtained in the preparation of vocabulary questions derived from theories related to vocabulary. Third, after obtaining several indicators, a vocabulary mastery question is drawn up which is also derived directly from the indicators that have been mutually agreed upon.Keywords: indicators; literature learning; vocabulary Abstrak: Kosakata merupakan hal penting yang harus dimiliki oleh seorang siswa dalam pelajaran Bahasa Indonesia tidak terkecuali dalam pelajaran sastra. Untuk mengukur sejauh mana penguasaan kosakata siswa guru perlu melakukan tes terhadap siswa. Sebelum melakukan tes tentunya guru memerlukan soal dalam mengukur penguasaan kosakata siswa. Fenomena yang ditemukan di lapangan adalah guru kurang memperhatikan indikator dalam pembuatan soal sastra. Hal tersebut menyebabkan soal yang dibuat tidak sesuai dengan kemampuan siswa sehingga hasil yang diharapkan tidak tercapai dengan baik. Kurang terampilnya guru dalam membuat soal sastra khususnya soal penguasaan kosakata ini disebabkan oleh beberapa faktor. Salah satu faktornya adalah kurangnya penataran dan pelatihan yang diberikan kepada guru. Tujuan Kegiatan PkM ini dilaksanakan untuk memberikan pemahaman kepada guru dalam melakukan penyusunan soal penguasaan kosakata dalam pembelajaran sastra. Ada beberapa simpulan yang dapat diambil setelah melakukan kegiatan pengabdian kepada masyarakat ini. Pertama, peserta kegiatan PkM (guru-guru tim MGMP tingkat SMA se Pekanbaru) sangat antusias mengikuti pelatihan ini. Kedua, setelah dilakukan pelatihan dan diskusi dengan guru-guru diperolelah empat indikator dalam penyusunan soal kosakata yang diturunkan dari teori yang berhubungan dengan kosakata. Ketiga, Setelah mendapat beberapa indikator disusunlah soal penguasaan kosakata yang juga diturunkan langsung dari indikator yang sudah disepakati bersama.Kata kunci: indicator; kosakata; pembelajaran sastra